Yabancı dil hazırlık eğitimi alan öğrencilerin yabancı dile yönelik kaygı ve başarıları arasındaki ilişkiler - Tuncer, Murat; Temur, Mehmet (My University, 2017)
Bu araştırmanın amacı İngilizce hazırlık eğitimi alan öğrencilerin yabancı dil ders kaygısına yönelik görüşlerinin değerlendirilmesidir. Araştırma tarama modeline göre yürütülmüştür. Araştırmada Horwitz, Horwitz ve Cope (1986) tarafından geliştirilen ve geçerlik-güvenirlik çalışması Gürsu (2011) tarafından yapılan İngilizce Dersine Yönelik Kaygı ölçeği kullanılmıştır. Araştırmada örneklem seçimi yoluna gidilmemiş, veri toplama araçlarının uygulandığı dönemde sınıflarında hazır bulunan bütün öğrenciler çalışmaya katılmışlardır. Araştırma sonucunda yabancı dil ders kaygısına yönelik görüşlerin cinsiyete göre ölçeğin yabancı dil ders kaygısı, dil dersinde konuşma kaygısı alt boyutları ve ölçeğin tamamı açısından kadın öğrenciler lehine istatistiksel olarak anlamlı düzeyde farklılaştığı belirlenmiştir. Yabancılarla Konuşma Kaygısı açısından ise yazma, okuma ve main course akademik başarı puanları ile düşük, anlamlı olmayan ilişkiler gözlenmiştir.

The main purpose of this study is to evaluate the students’ views, receiving foreign language preparation education, in terms of course anxiety. The study was conducted according to the descriptive survey modal. In the study, a Scale Bearing English Course anxiety developed by Horwitz ,Horwitz and Cope(1986) and its validity and reliability analysis tested and adapted by Gürsu (2011) was used. In this survey, the sample was not chosen, and data collection was gathered from all prep school participants present in their classes at the time of the research data collecting instruments were carried out. According to the statistical analysis of research’s findings, when foreign language course anxiety in class, and its sub-dimensions of speaking anxiety in foreign language class and its complete scale was put into consideration in terms of genders, a significant difference was identified in favor of women. Non-significant correlations were observed in students’ academic achievement score related to reading writing and main course elements in terms of Speaking with Foreigners Anxiety. Anxiety was again determined in this research that had important influence as variables on learning and teaching processes.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hazırlık eğitimi; Kaygı; Yabancı dil ders kaygısı; İngilizce eğitimi; Prep education; Anxiety; Foreign language course anxiety; English language education